The effect of social anxiety on the mental well-being of sport sciences students - Agrali Ermis, Sermin; Toros, Turhan; Serin, Emre; Akbulut, Alperen; Kara, Tayfun; Uzun, Meliha (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study aimed to examine the impact of social anxiety levels on the mental well-being of students of Sport Sciences. The research was conducted using a relational survey model and involved 253 students enrolled in the Faculty of Sport Sciences at a public university in the Aegean region of Turkey. Data were collected through a personal information form, the Liebowitz Social Anxiety Scale, and the Warwick-Edinburgh Mental Well-Being Scale, and analyzed using SPSS. The findings indicate that social anxiety can affect students’ academic and athletic performance. However, no direct significant relationship was found between social anxiety and mental well-being (p>0.05). Nonetheless, it was determined that students who actively engage in sports exhibit lower levels of social anxiety and higher levels of mental well-being (p<0.05). Additionally, variables such as department of study, academic year, and living arrangements were found to have varying effects on mental well-being. In conclusion, physical activity contributes positively to students’ psychological health, and the impact of social anxiety on mental well-being appears to be indirect.